2014
DOI: 10.1080/02188791.2014.881318
|View full text |Cite
|
Sign up to set email alerts
|

Pathway from vocational education and associate degree to higher education: Chinese international students in Australia

Abstract: Understanding factors influencing international students' decision to engage in international education is essential for education providers to better cater for students' educational expectations and enhance their attractiveness to international students. Whilst there has been extensive research on the reasons why international students undertake cross-border higher education, international students' motivations for enrolling in vocational education and associate degree programmes are still underresearched. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This participant's observation is supported by the World Bank (2012) report, which establishes that one of the critical problems facing East Asian countries is the disconnection between the education system and the labour market, with the paradox of a high unemployment rate among university graduates and unfilled positions in trades. Yet, despite this paradox, the main obstacle to vocational education choice seems to be associated with parents' attitudes towards vocational credentials or the social stigma associated with the image of vocational education and trades in many countries (Cao and Tran 2014;Kingston 2008). Based on a study with employers and parents in both developed and developing countries, Kingston (2008) found that many parents do not appear to support their children's pursuit of vocational education; instead, an academic route is more favoured.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…This participant's observation is supported by the World Bank (2012) report, which establishes that one of the critical problems facing East Asian countries is the disconnection between the education system and the labour market, with the paradox of a high unemployment rate among university graduates and unfilled positions in trades. Yet, despite this paradox, the main obstacle to vocational education choice seems to be associated with parents' attitudes towards vocational credentials or the social stigma associated with the image of vocational education and trades in many countries (Cao and Tran 2014;Kingston 2008). Based on a study with employers and parents in both developed and developing countries, Kingston (2008) found that many parents do not appear to support their children's pursuit of vocational education; instead, an academic route is more favoured.…”
Section: Methodsmentioning
confidence: 97%
“…The growing wealth and size of the middle class in a number of primary source countries, including China, India and Vietnam, is one of the important drivers of international student mobility. Pursuing international education can be a solution for children of middle-class families who fail to secure tertiary places in their home countries due to the gap between demand and supply in tertiary education (Cao and Tran 2014). In Vietnam, for example, the number of students who registered for kỳ thi đại học (the national higher education entrance examination) reached 1.8 million in 2012 (VnExpress 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Academic requirement and attainments Xiao (2013) McCrohon and Nyland (2018) Y. Wang (2013) L. Cao and Tran (2015) J. Wu (2012) He (2017) Miao ( Australia can acquire knowledge, including job market information and entrepreneurial endeavor.…”
Section: Study Languagementioning
confidence: 99%
“…Wang, 2013). Although Australian higher education has relatively low entry requirements, Australia has abundant qualified education recourses (L. Cao & Tran, 2015). Looking into various university rankings, Australia has the third largest number of top universities, following the United States and the United Kingdom, indicating that Australian universities have good academic reputation in the world (Mazzarol, Soutar, Smart, & Choo, 2001;McCrohon & Nyland, 2018;C.…”
mentioning
confidence: 99%
See 1 more Smart Citation